International Journal of Disability and Social Justice - Beckett, Angharad E. (Pluto Journals, 2021)
The International Journal of Disability and Social Justice (IJDSJ) is a new international and interdisciplinary journal in the field of Disability Studies, providing an outlet for scholars and academic-activists. Launching in 2021, the Journal will be of interest and use to the broader community of disabled people and their allies, who are working to challenge injustices and build inclusive societies. The Journal and its companion Digest (an open-access publication published alongside with summaries of articles) will publish cutting-edge scholarship and research by authors concerned with challenging injustices related to disability.
Keywords: Social justice